Management of benign vulval dermatoses in primary care. Issue 5 (May 2018) - Patel, Mitesh; Nunns, David
Abstract : Vulval dermatoses can be difficult to manage in primary care, and GPs need to be aware of the risk of malignancy. This article describes the most common types of benign vulval dermatoses encountered in primary care and their management, and discusses when referral to secondary care is required.